An Unmanned Sweeper Path Planning Algorithm for Structured Roads - Lei He; Baoyun Wang; Yunshan Peng; Xiucai Zhang (IEEE Access, 2024)
This paper presents a path planning algorithm to address the issue of current traversal planning algorithms being unsuitable for lane traversal by unmanned sweepers on structured roads. The algorithm treats lanes in structured roads as nodes and utilizes the A* algorithm to compute the path distances between all lane nodes, constructing a cost matrix, and the pre-traversal lane node sequence is found through the heuristic algorithm. The A* algorithm is then used to search for the shortest path between adjacent pre-traversal lane nodes, and this shortest path lane sequence is added to the pre-traversal node sequence. Pruning optimization is applied to the obtained node sequence, generating the optimal lane traversal node sequence and converting it to the corresponding lanes to achieve the structured road lane traversal. Experimental results in various structured road scenarios indicate that the proposed algorithm can effectively and completely traverse structured roads.